IMPLEMENTASI SUPERVISI KLINIS DIFERENSIASI DALAM MENINGKATKAN KUALITAS PEDAGOGIS PENDIDIK PENDIDIKAN ANAK USIA DINI: STUDI KASUS DI TK MUBAROK SALATIGA - R. Rety Riesmawati Riesmawati; Maryani Maryani; Setiawati Setiawati; Soedjono Soedjono (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of differentiated clinical supervision in improving the pedagogical quality of early childhood education teachers at TK Mubarok Salatiga. The research is grounded in the existing gap in the quality of early childhood educators in Indonesia, where many teachers have not met the minimum academic qualification requirements, as well as the limited number of studies that specifically examine clinical supervision using a differentiated approach. Employing a qualitative case study design, the research involved the principal, six teachers, foundation representatives, and parents selected through purposive sampling. Data were collected through observations, in-depth interviews, and document analysis. The findings reveal that differentiated clinical supervision is implemented through systematic planning, execution across pre-conference, classroom observation, and post-conference stages, and the application of directive, collaborative, and non-directive approaches tailored to teachers’ characteristics. The results also show that differentiated clinical supervision significantly enhances teaching quality, teachers’ pedagogical competence, and their motivation to pursue higher academic qualifications.